The Reference Diet Deprivation (ReDD) index: a single indicator to measure the incidence, breadth and depth of diet deprivation across multiple essential food groups, with case study in Nigeria - CGIAR Research Program on Policies, Institutions, and Markets (2021)
This innovation was introduced in a Discussion Paper published in December 2021.